Effect Estimate of Time-varying Social Support and Trust on the Physical and Mental Health of Mothers at 2.5 Years Postpartum: The Japan Environment and Children’s Study (JECS) - Kenta Matsumura; Ryoko Morozumi; Kei Hamazaki; Akiko Tsuchida; Hidekuni Inadera (Journal of Epidemiology, 2023)
Background: Many epidemiological studies have reported the association between various social factors and health status in mothers during and after pregnancy. However, little is known about their joint and longitudinal impact. We examined the association of lack of social support and trust during pregnancy and at 2.5 years postpartum with health status in mothers. Methods: To adequately address time-varying exposure, marginal structural models were fitted to a pseudopopulation constructed using inverse probability weighting. The model included records of 90,071 mothers participating in the Japan Environment and Children’s Study. Social support and trust were measured using a 9-item questionnaire (Q1–9). Mental and physical health were measured using Mental and Physical Component Summary scores from the 8-item Short-Form Health Survey. Results: For the Mental Component Summary, the magnitude of the effect estimate was largest when participants lacked close friends/neighbors (Q4) at only 2.5 years postpartum (effect estimate, −6.23), followed by a lack in emotional support (Q2) at the same time point (effect estimate, −4.94). For the Physical Component Summary, effect estimates were negligible. The magnitude of the effect estimates of lack of social support and trust tended to be larger when there was a lack at only 2.5 years postpartum than at both time points. Conclusion: These findings suggest that, after childbirth, a loss in social support, particularly in an emotional aspect, carries high risk, especially for mental health. Our results highlight the importance of supporting mothers for more than a few years after pregnancy.